Submaximal Accentuated Eccentric Jump Training Improves Punching Performance and Countermovement Jump Force–Time Variables in Amateur Boxers - Herrera-Valenzuela, T; Aedo-Munoz, E; Sanchez-Ramirez, C; Cid-Calfucura, I (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
Objective: This study aimed to identify the effects of a submaximal jump training program using accentuated eccentric loading (AEL) on punching performance and countermovement jump (CMJ) force–time characteristics in amateur boxers. Methods: Twenty-nine amateur boxers (age: 24.9 ± 5.4 years; height of 175.9 ± 5.2 cm; body mass: 76.2 ± 10.5 kg) were randomly assigned to three groups: AEL group (n = 9), CMJ group (n = 10), and control group (n = 10). The AEL group performed countermovement jumps using handheld dumbbells equivalent to 10–20% of body mass, followed by unloaded concentric phases. All participants were evaluated pre- and post-intervention on punching peak force and countermovement jump performance. Results: Significant differences were found in favor of the AEL group for the peak force of the jab punch (pre: 1050 ± 203; post: 1158 ± 189 N), straight punch (pre: 1685 ± 393; post: 1861 ± 429 N), right cross punch (pre: 2005 ± 362; post: 2150 ± 417 N), and left cross punch (pre: 1836 ± 312; post: 1977 ± 393 N), along with greater gains in jump height, propulsive impulse, and absolute and relative peak power than the CMJ and control groups. Conclusions: A submaximal accentuated eccentric jump training program enhances punching peak force and lower-limb power output in amateur boxers, offering a practical strategy for improving power-oriented performance during preparatory training phases. © 2025 by the authors.